(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
The sequence soz auku arestalo tamai lacks a verb. As a whole sentence, its structure consists of a neuter nom.-ac. pronoun which plays the role of the subject, a predicative auku and a complement introducing a causal specification. It refers to the former part of the text and means “this is firm, following the directions of the authorities”.